2015
DOI: 10.1002/ajp.22360
|View full text |Cite
|
Sign up to set email alerts
|

To pair or not to pair: Sources of social variability with white‐faced saki monkeys (Pithecia pithecia) as a case study

Abstract: Intraspecific variability in social systems is gaining increased recognition in primatology. Many primate species display variability in pair-living social organizations through incorporating extra adults into the group. While numerous models exist to explain primate pair-living, our tools to assess how and why variation in this trait occurs are currently limited. Here I outline an approach which: (i) utilizes conceptual models to identify the selective forces driving pair-living; (ii) outlines novel possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 109 publications
(155 reference statements)
0
15
0
Order By: Relevance
“…On the other hand, if extra males are indeed beneficial for more effectively defending resources, females or infants against outside individuals [Thompson, 2015], it is unclear why the males would have jointly abandoned a well-established territory, two reproductive-age females and a newborn infant, without being challenged. Although the males ranged partially outside of the group's territory, they also ranged within it and they returned to this territory and to the resident females twice.…”
Section: Potential Functions Of Saki Groups With Multiple Malesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, if extra males are indeed beneficial for more effectively defending resources, females or infants against outside individuals [Thompson, 2015], it is unclear why the males would have jointly abandoned a well-established territory, two reproductive-age females and a newborn infant, without being challenged. Although the males ranged partially outside of the group's territory, they also ranged within it and they returned to this territory and to the resident females twice.…”
Section: Potential Functions Of Saki Groups With Multiple Malesmentioning
confidence: 99%
“…Joint mate and/or territorial defense may be especially important if floaters (i.e. solitary individuals without territories of their own) are prevalent in the area [Port and Johnstone, 2013;Thompson, 2015]. Indeed, a study of Azara's owl monkeys (Aotus azarai) revealed that encounters with floaters can lead to high turnover rates among pair-mates [Fernandez-Duque and Huck, 2013].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saki monkeys are considered to be pair-living primates that also occasionally live in groups with multiple adults of one or both sexes [reviewed in Norconk and Setz, 2013;Van Belle et al, 2015;Thompson, 2016]. Sakis have been reported to retain adult offspring [Thompson et al, 2010;Norconk, 2011] and to accept putatively nonrelated adult immigrants into the group [Porter et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…The extent of intraspecific variability or phenotypic plasticity in these species, traditionally defined as monogamous, has emerged as a key issue [Thompson, 2015; Garber et al, this issue; Diaz-Munoz, this issue] in the study of monogamy. A prominent example has been variability in callitrichid (marmoset and tamarin) groups in the wild, which have been described as monogamous [Kleiman 1977, 1979; Leutenegger 1980; Baker et al 1993], polyandrous [Goldizen 1987; Sussman and Garber 1987], and “flexible” [Goldizen 1988; Caine 1993].…”
Section: Introductionmentioning
confidence: 99%